The Uses of Phenomenology for Latinx Feminisms: Developing a Phenomenological Approach Informed by Rupture - Erika Grimm (Philosophies)
Given the various shortcomings of classical phenomenological methods identified by critical and liberatory theorists, this paper considers what phenomenology has to offer theorists of multiply marginalized experience. The paper begins with an account of the major reasons for which Latinx feminists such as Linda Martín Alcoff, Jacqueline Martinez, and Mariana Ortega have found a phenomenological approach useful in their projects. This account reveals that though Latinx feminist phenomenologists have found useful resources for theorizing multiply marginalized theory and identity in the classical texts of phenomenology, experiences unique to those subjected to marginalization remain significantly underdeveloped or absent from classical accounts. Taking seriously the primacy of lived experiences of ‘rupture’, this paper argues, is therefore necessary in the development of a phenomenological approach that does justice to life in the borderlands and the lived experience of being-between-worlds. Informed by the work of Latinx feminist theorists such as Gloria Anzaldúa and María Lugones, this paper closes with a proposed critical feminist phenomenological approach that centers the moment of ‘rupture’ described in such work. Ultimately, this paper argues that the communication and documentation of these ruptures in the form of phenomenological description allows for the examination and interrogation of sedimented logics of oppression on the way to liberatory ends.